KONSTRUKSI IDEOLOGI DALAM WACANA KEAGAMAAN JARINGAN ISLAM LIBERAL (JIL) - Firman, Firman; Santoso, Anang; Dawud, Dawud (LITERA, 2016)
This study aims to describe the ideological construction in the Liberal Islam Network (LIN)’s religious discourses through lexico-grammatical features, namely vocabulary, grammar, and text structure. This was a qualitative study employing the critical discourse analysis approach. The research data were words, phrases, clauses, sentences, and paragraphs. The data sources were texts from articles, reports, comments, press releases, and rubrics produced and published by LIN through www.islamlib.com. The findings show that the lexico-grammatical features are used to construct LIN’s ideology. Vocabulary includes classification, lexicalization, meaning relations, and metaphors. Grammar includes sentence modes, modality, personal pronouns, and passivization. Text structure includes interactional convention with participant control and text arrangement and sequencing. Interaction convention includes confirmation, topic direction, and formulation. Text arrangement and sequencing use general patterns and development patterns.